Pelatihan Pembuatan Pupuk Organik dengan Biokomposter di lingkungan SMP Negeri 40 Makassar - Rosmini M.; Haris, Haris; Aldhila Gusta H. Y.; Midsar A.; Arfandi Maru (Jurnal Pengabdian Masyarakat, 2025)
The community service activity entitled "Training on Making Organic Fertilizer with Biocomposters at SMP Negeri 40 Makassar" aims to increase the knowledge, skills, and environmental awareness of teachers and students in managing organic waste. This program applies a participatory approach and project-based learning through three main stages, namely preparation, training, and mentoring. A total of 50 participants consisting of teachers, students, and cleaning staff participated in direct training on the theory and operation of biocomposters. The results of the activity showed an increase in participants' knowledge by 42.2% and a decrease in the volume of organic waste by up to 57%. The biocomposter produces 65 kg of solid compost and 15 liters of liquid organic fertilizer within 21 days. In addition, the School Biocomposter Management Team (TPBS) was formed as an effort to sustain the program. The implementation of biocomposters not only reduces waste generation, but also creates a greener and cleaner school environment, while strengthening environmental education practices that are in line with the Adiwiyata program and the Sustainable Development Goals (SDGs) points 11 and 13. This program is expected to be a school-based waste management model that can be replicated in other educational institutions.